P072: Preventing emergency department visits among patients with cancer: a scoping review. (May 2020) - Kirkland, S.; Clua, M. Garrido; Junqueira, D.; Campbell, S.; Rowe, B.
Abstract : Introduction: Patients frequently present to the Emergency Department (ED) with predictable complications associated with radiation and chemotherapy for active cancer. Care alternatives have been proposed to reduce ED visits; however, no systematic review related to ED presentations has been completed. The objective of this scoping review was to examine the effectiveness of interventions designed to reduce ED visits among patients receiving active cancer treatment. Methods: A comprehensive literature search involving nine electronic databases and the grey literature was completed. Inclusion criteria considered studies assessing the impact of any intervention to reduce ED utilization among patients with active cancer. Two reviewers independently assessed relevance and inclusion; disagreements were resolved through third party adjudication. Dichotomous and continuous outcomes were summarized as risk ratio (RR) or mean difference (MD) with 95% confidence intervals (CIs) using a random-effects model, wherever appropriate. Results: From 3303 citations, a total of 25 studies were included. Interventions identified in these studies comprised: routine and symptom-based patient follow-up, oncology outpatient clinics, early symptom detection, comprehensive inpatient management, hospital at home, and patient navigators. Six out of eight studies assessing oncology outpatient clinics reported a decrease in the proportion of patients presenting to the ED. A meta-analysis of three of these studies did not demonstrate reduction in ED utilization (RR 0.78; 95% CI: 0.56 to 1.08; I2 = 77%) when comparing oncology outpatient clinics to standard care; however, sensitivity analysis removing one study reporting rare events supported a decrease in ED visits (RR 0.86; 95% CI: 0.74 to 0.99; I2 = 47%). Three studies assessing patient follow-up interventions showed no difference in ED utilization (RR 0.69; 95% CI: 0.38 to 1.25; I2 = 86%). Conclusion: A variety of interventions designed to mitigate ED presentations by patients receiving active cancer treatment have been developed and evaluated. Limited evidence suggests that an oncology outpatient clinic may be an effective strategy to reduce ED utilization; however, additional high-quality studies are needed.